Hacia una breve concepción integral del sufrimiento (2018)
In this article it is gathered the opinion of many academic references of different areas of knowledge as existential philosophy, medicine, anthropology, psychology, etc. from which the understandings of the concept of suffering have been constructed, which gives way to the final signaling of the necessity of an extended practice in relation to the experiential and epistemic discovery of the being in the suffering; this article can be considered as the encounter of a journey where the modification of the meaning of the term is evidenced and how the experience has given an important construct when giving an integral conception. Starting from the manifest fact of the existence of pain and suffering, the possibility of giving the reader an integral perspective, which facilitates the understanding of this concept from the different knowledge that was worked for the accomplishment of the text and thus to emphasize the convergences and divergences that have the different meanings of this term